2018
DOI: 10.1155/2018/3740461
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts of Neurodegenerative Mechanisms in Alzheimer’s Disease

Abstract: Neurodegenerative diseases are hereditary or sporadic conditions that result in the progressive loss of the structure and function of neurons as well as neuronal death. Although a range of diseases lie under this umbrella term, Alzheimer's disease (AD) and Parkinson's disease (PD) are the most common neurodegenerative diseases that affect a large population around the globe. Alzheimer's disease is characterized by the abnormal accumulation of extracellular amyloid-β plaques and intraneuronal neurofibrillary ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 79 publications
(78 reference statements)
1
84
0
3
Order By: Relevance
“…While Aβ 1‐40 is abundant and less neurotoxic, Aβ 1‐42 is less abundant and severely neurotoxic as well as more prone to aggregate to amyloid plaques (Tiwari, Atluri, Kaushik, & Yndart, ). Extracellular deposits of these Aβ peptides in brain tissue are considered as one of the key hallmarks of Alzheimer's disease (AD), which is the most common form of age‐related neurodegenerative disease (Magalingam, Radhakrishnan, Ping, & Haleagrahara, ). It has been shown that high levels of chronic inflammation measured by, for instance, acute‐phase reactants [i.e.…”
Section: Introductionmentioning
confidence: 99%
“…While Aβ 1‐40 is abundant and less neurotoxic, Aβ 1‐42 is less abundant and severely neurotoxic as well as more prone to aggregate to amyloid plaques (Tiwari, Atluri, Kaushik, & Yndart, ). Extracellular deposits of these Aβ peptides in brain tissue are considered as one of the key hallmarks of Alzheimer's disease (AD), which is the most common form of age‐related neurodegenerative disease (Magalingam, Radhakrishnan, Ping, & Haleagrahara, ). It has been shown that high levels of chronic inflammation measured by, for instance, acute‐phase reactants [i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified multiple neurodegenerative pathways that result in a domino-like cascade of events that eventually lead to the development of dementias. However, these changes are not seen in all cases of AD [17,18].…”
mentioning
confidence: 86%
“…Recent research has identified multiple neurodegenerative pathways that result in a domino‐like cascade of events that eventually lead to the development of dementias. However, these changes are not seen in all cases of AD [17,18]. The characteristic features of AD are the pathological accumulation of extracellular plaques composed of amyloid‐β (Aβ) protein and intraneuronal tangles consisting of altered forms of tau [17].…”
Section: Better Understanding Selective Neuronal Vulnerability and Rementioning
confidence: 99%
See 1 more Smart Citation
“…The antioxdant and free radicals of lipid peroxidation and cognition, and cognitive response to an exercise intervention program, in adults with coronary artery disease at risk of dementia [63]. The brain is more susceptible to lipid peroxidation due to its high oxygen consumption, high level of redox metal ions, reduced antioxidant defense mechanism, and high level of polyunsaturated fatty acids [64].…”
Section: Free Radical Cause Lipid Peroxidationmentioning
confidence: 99%